Venture capital, double-sided adverse selection, and double-sided moral hazard - Eike Houben (Universität Kiel, Institut für Betriebswirtschaftslehre, 2002)
The paper offers a new explanation for the widely observed use of redeemable and convertible preferred stock in venture capital finance. Redeemable and convertible preferred stocks can be used to endogenously allocate cash flow and control rights as a function of the state of nature, the entrepreneur's and venture capitalist's effort, and the signals each player has revealed about his private information regarding the project's perspectives. This property can be used to induce both players to reveal their private information truthfully and to spend the efficient effort. This result holds irrespective of the assumed distribution function of the state of nature. The model is consistent with the observation that conversion is often automatic and that there is an inverse correlation between risk and control rights. Furthermore, it explains why venture capitalists can earn positive expected returns in a competitive venture capital market.
Keywords: D23; D82; G24; G32; 650; venture capital; moral hazard; adverse selection; signaling